Suami Mafqud Dan Status Pernikahan Studi Komparatif Antara Mazhab Maliki Dan Mazhab Syafii - Hasbi Ash Shiddiqi; Fajrih Fajrih (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
One of the various reasons underlying the breakdown of a marriage is the departure or disappearance of the husband from the wife (mafqud). The issue of a husband's mafqud is a complicated and difficult problem because of course the absence or disappearance of a husband can cause misery to the people left behind who are his responsibility, especially his wife. On the issue of a husband's mafqud, each mujtahid has a different view. Imam Maliki and Imam Syafii are among those who have different views on this case. Therefore, in this research we will discuss what is the opinion of the Imam Maliki School regarding mafqud husbands and their marital status?, and what is the opinion of the Imam Syafii School regarding mafqud husbands and their marital status? The purpose of writing this thesis is to find out what the Imam Maliki School thinks about mafqud husbands and their marital status, as well as to find out what Imam Syafii Mahab thinks about mafqud husbands and their marital status. The type of research used in this thesis is qualitative research in the form of a library review, the primary data source is the books al-muwwatha' and al-Umm, while the secondary data sources are al-Fiqh Wa Adillatuhu, Bidayah al-Mujtahid Wa Nihayah al -Mustaqhid, Fiqh al-Sunah, al-Muhazab, al-Muntaqa Syarakh al-Muwwatha', Qawain al-Fiqhiyah, Munakahat fiqh books, Al-Qur'an translated by the Department of Religion, journals, and other appropriate literature with research themes.